Staining Cells with Extracts Prepared from Flowers of Bougainvillea X Buttiana. - Paul Towet (Student's Journal of Health Research, 2020)
Background:     Staining is the application of dyes to specimens to impart colour to cells through a chemical reaction. The study aimed at finding plant extracts to stain human blood cells, stem sections of Amaranthus species, Gram-negative organisms such as Escherichia coli, and Gram-positive organisms such as Staphylococcus aureus.     Methodology:     Healthy mature flowers of Bougainvillea X buttiana and Amaranthus species plants were picked from gardens around the University of Kisubi. Bracts of Bougainvillea X buttiana were separated from other flower parts and air-dried. Both negative and positive controls for cells were prepared.     Results:     White blood cells, platelets, and cells of Escherichia Coli and Staphylococcus aureus did not stain under all treatments with the extracts while human red blood cells and stem sections of Amaranthus species stained under certain treatments with the extracts. The extracts were more successful in staining stem sections of Amaranthus species as compared to human red blood cells where staining occurred in very few circumstances. Stem sections of Amaranthus species required shorter to stain effectively while human red blood cells required longer to stain effectively.   Conclusion:   Extracts of the bracts of Bougainvillea X  can be experimented with various cells when their pH is neutral and alkaline.